2023
DOI: 10.1038/s41598-023-47795-1
|View full text |Cite
|
Sign up to set email alerts
|

High viral suppression and detection of dolutegravir-resistance associated mutations in treatment-experienced Tanzanian adults living with HIV-1 in Dar es Salaam

George M. Bwire,
Beatrice Godwin Aiko,
Idda H. Mosha
et al.

Abstract: To curb HIV infection rate in Tanzania, antiretroviral therapy (ART) has been scaled up since 2006, and in 2019, the country shifted to regimen including dolutegravir as a default first line. We assessed the success of ART and the contribution of HIV drug resistance (HIVDR) to unsuppressed viral loads. Between February and May 2023 a cross-sectional survey with random sampling was conducted in the six clinics in an urban cohort in Dar es Salaam. Patients with unsuppresed viral loads (local criteria viral load … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In a study from Nigeria, GRT was performed on 33 samples from 281 individuals with VF [ 71 ]. In three studies from Tanzania, GRT was performed in nearly all of the 181 individuals with VF [ 72 , 73 , 74 ]. Among the estimated 214 individuals in these five studies undergoing GRT, 19 (8.9%) developed an INSTI DRM—most commonly G118R and R263K.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study from Nigeria, GRT was performed on 33 samples from 281 individuals with VF [ 71 ]. In three studies from Tanzania, GRT was performed in nearly all of the 181 individuals with VF [ 72 , 73 , 74 ]. Among the estimated 214 individuals in these five studies undergoing GRT, 19 (8.9%) developed an INSTI DRM—most commonly G118R and R263K.…”
Section: Resultsmentioning
confidence: 99%
“…We described six such studies including one from Brazil of 113 PLWH with confirmed VF on a first-line regimen of DTG plus two NRTIs [ 42 ] and five from Sub-Saharan Africa. The studies from Sub-Saharan Africa included approximately 214 individuals, most of whom had prior ART experience before initiating DTG treatment [ 70 , 71 , 72 , 73 , 74 ]. The study from Brazil found that approximately six percent of the samples tested were found to have INSTI DRMs, whereas in the studies from Sub-Saharan Africa, approximately nine percent of the samples tested had INSTI DRMs.…”
Section: Discussionmentioning
confidence: 99%
“…be highly effective and tolerable as compared to efavirenz-based regimen. 14,16,55,56 Being male was associated with increased odds of having VNS, suggesting potential gender-related disparities in VNS. The high rates of VNS among males compared to females in some contexts could be attributed to societal expectations around masculinity that often discourage men from seeking healthcare 57…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Nigeria, GRT was performed on 33 samples from 281 individuals with VF [73]. In three studies from Tanzania, GRT was performed in nearly all of the 181 individuals with VF [74][75][76]. Among the estimated 214 individuals in these five studies undergoing GRT, 19 (8.9%) developed an INSTI DRM -most commonly G118R and R263K.…”
Section: Art-experienced Plwh With a History Of Vf On An Nnrti-contai...mentioning
confidence: 99%
“…We described six such studies including one from Brazil of 113 PLWH with confirmed VF on a first-line regimen of DTG plus two NRTIs [42] and five from Sub-Saharan Africa. The studies from Sub-Saharan Africa included approximately 214 individuals most of whom had prior ART experience before initiating DTG treatment [72][73][74][75][76]. The study from Brazil found that approximately six percent of the samples tested were found to have INSTI DRMs while in the studies from Sub-Saharan Africa, approximately nine percent of the samples tested had INSTI DRMs.…”
Section: Dtg Monotherapymentioning
confidence: 99%